Different Active Sites of LaCoO3 and LaMnO3 for CH4 Oxidation by Regulation of Precursor’s Ion Concentration - Saifei Wang; Yiyuan Zhang; Peiqi Chu; Jie Liu; Man Wang; Peng Zhang; Erhong Duan (The Global Environmental Engineers, 2020)
Pure LaCoO3 and LaMnO3 were synthesized under different ion concentrations of precursors and the difference of active sites for CH4 oxidation between them was found. As the ion concentration of precursors increased, the two kind of perovskite crystals grew larger along with agglomerate. Meanwhile, LaCoO3 and LaMnO3 prepared by high ion concentrations of precursors enriched more surface Co3+ or Mn4+. The catalytic activity of the catalysts was tested in the oxidation reaction of methane under fuel-lean condition, results showed that LC-1.0 and LM-2.0 had the optimal activity and the light-off temperatures were 492°C and 486°C, respectively. Combining the physical and chemical characterization, the LaCoO3 and LaMnO3 possess different active sites for the methane catalytic reaction, and the conclusion was further verified by the DFT simulation. For LaCoO3, the surface lattice oxygen is the main active site, while for LaMnO3, the reaction is facilitated by the high-valent manganese.